2021
DOI: 10.1097/scs.0000000000008146
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Medial Canthal Defects by Local/Loco-Regional Flaps

Abstract: area, forehead, and cheek. But the same color and texture are an advantage. CONCLUSIONSMedial canthal defects are best managed by adjacent local/locoregional flaps from the glabella, nasolabial area, forehead, and cheek region as they provide a better color match and texture as compared to skin graft. The result is cosmetically better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…However, it is difficult to reproduce the natural depression of the medial canthal region, and problems such as skin mismatch, bulging of the skin flap, scarring in the forehead area, and narrowing between the eyebrows can occur 4,9 . When skin flaps are taken from areas other than the eyelid, such as the forehead or nose, reconstructing the characteristic medial canthal region skin is difficult, and scarring of the harvested area remains a problem 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to reproduce the natural depression of the medial canthal region, and problems such as skin mismatch, bulging of the skin flap, scarring in the forehead area, and narrowing between the eyebrows can occur 4,9 . When skin flaps are taken from areas other than the eyelid, such as the forehead or nose, reconstructing the characteristic medial canthal region skin is difficult, and scarring of the harvested area remains a problem 10 …”
Section: Discussionmentioning
confidence: 99%
“…4,9 When skin flaps are taken from areas other than the eyelid, such as the forehead or nose, reconstructing the characteristic medial canthal region skin is difficult, and scarring of the harvested area remains a problem. 10 A hug is a common expression of affection. When using the hug flap technique, the 2 skin flaps of the upper and lower eyelids are moved to cover the defect in a manner similar to a hug (hence, the name "hug flap").…”
Section: Discussionmentioning
confidence: 99%
“… 14 In addition, for defects in the lower medial canthal region, a VY advancement flap from the nasolabial region gives excellent results. 15 Finally, for full-thickness medial canthal defects, Motomura et al 16 have demonstrated the combined use of a palatal mucoperiosteal graft, advancement flaps, and cheek flaps to get adequate closure.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been reported in Literature for the reconstruction of medial canthal region: direct closure or second intention healing for small defects, skin grafts, local and regional transposition or rotational flaps. 7 However, grafts often result in a patchy appearance, due to mismatch in colour and texture. When tumour excision leaves the underlying bone or tendon exposed, a skin graft is not a viable option.…”
mentioning
confidence: 99%